Inverse fractional Sturm-Liouville problem with eigenparameter in the boundary conditions - Sa'idu, Auwalu; Koyunbakan, Hikmet (Wiley, 2022)
Ambarzumyan theorem is one of the first results of the inverse spectral theory. In this work, Ambarzumyan's theorem is proved for a fractional derivative Sturm-Liouville problem. In addition, a general function that depends on the eigenvalue parameter under boundary conditions is considered.
Keywords: Ambarzumyan theorem; eigenparameter; fractional Sturm-Liouville problem; spectrum